DEPRESSION AND ASSOCIATED SOCIO DEMOGRAPHIC FACTORS AMONG PERSONNEL REPORTING TO A FIELD HOSPITAL FOR ROUTINE MEDICAL CARE - Ahmed, Muzafar; Maher, Muhammad Ramzan; Muhammad Farooq; Abbasi, Nasser Ahmed; Fatima, Nazish; Iqbal, Syeda Saira (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the prevalence of depression and associated socio demographic factors among personnel reporting to a field hospital in Sudan for routine medical care and analyze socio demographic factors associated with depressive symptoms. Study Design: Cross sectional descriptive study. Place and Duration of Study: This study was conducted in a field hospital, from Apr 2015 to Mar 2016 in Sudan. Methodology: The sample population comprised of 226 personnel who reported to the hospital for routine medical care. Beck Depression Inventory (BDI) was used to record the presence and severity of depressive symptoms. The following socio-demographic variables (rank, age, gender, ethnicity, education, marital status, socioeconomic status, family type, service in mission area, smoking habits, living conditions, lack of social support) were taken on a separate sheet. Results: Out of 226 subjects 58.4% had no depressive symptoms, 15.5% had mild, 21.2% had moderate and 4.9% had severe depressive symptoms. Unsatisfied with living condition in mission area, having more than 6 months of service and lack of social support were correlated with depressive symptoms. Tobacco smoking was highly associated with depression, while female gender and low education had a weak association with depressive disorder. Conclusion: The high prevalence of depressive symptoms in our study highlights the importance of developing good mental health care facilities for personnel deployed on different missions.